Changing clinical trends in 10 000 robot‐assisted laparoscopic prostatectomy patients and impact of the 2012 US Preventive Services Task Force's statement against PSA screening. (1st August 2019) - Onol, Fikret F.; P. Ganapathi, Hariharan; Rogers, Travis; Palmer, Kenneth; Coughlin, Geoff; Samavedi, Srinivas; Coelho, Rafael; Jenson, Cathy; Sandri, Marco; Rocco, Bernardo; Patel, Vipul
Abstract : Objectives: To evaluate the clinical trend changes in our robot‐assisted laparoscopic prostatectomy (RALP) practice and to investigate the effect of 2012 US Preventive Services Task Force (USPSTF) statement against PSA screening on these trends. Patients and Methods: Data of 10 000 RALPs performed by a single surgeon between 2002 and 2017 were retrospectively analysed. Time trends in successive 1000 cases for clinical, surgical and pathological characteristics were analysed with linear and logistic regression. Time‐trend changes before and after the USPSTF's statement were compared using a logistic regression model and likelihood‐ratio test. Results: Unfavourable cancer characteristics rate, including D'Amico high risk, pathological non‐organ‐confined disease and Gleason score ≥4+4 increased from 11.5% to 23.3%, 14% to 42.5%, and 7.7% to 20.9%, respectively, over time (all P < 0.001). Significant time‐trend changes were detected after the USPSTF's statement with an increase in the positive trend of Gleason ≥4+4 and increase in the negative trends of Gleason ≤3+4 tumours. There was a significant negative trend in the rate of full nerve‐sparing (NS) with a decrease from 59.3% to 35.7%, and a significant positive trend in partial NS with an increase from 15.8% to 62.5% over time (both P < 0.001). The time‐trend slope in 'high‐grade' partial NS significantly decreased and 'low‐grade' partial NS significantly increased after the USPSTF's statement. The overall positive surgical margin rate increased from 14.6% to 20.3% in the first vs last 1000 cases ( P < 0.001), with a significant positive slope after the USPSTF's statement. Conclusions: The proportion of high‐risk patients increased in our series over time with a significant impact of the USPSTF's statement on pathological time trends. This stage migration resulted in decreased utilisation of high‐quality NS and increased performance of poor‐quality NS.